2010
DOI: 10.3109/17483107.2010.481773
|View full text |Cite
|
Sign up to set email alerts
|

Using assistive technology for schoolwork: the experience of children with physical disabilities

Abstract: All of the children recognised that assistive technology enabled them to participate and reduced the impact of their physical disability, allowing independent participation, and facilitated higher learning outcomes. Issues related to ease of use, social implications and assistive technology systems are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…This is also recognised by Murchland and Parkyn (2010), which describes how it is the assistive technology that provides enhanced status rather than the pupil. But in this study, it is not necessarily just the eye gaze technology itself that has enhanced status.…”
Section: Results Discussionmentioning
confidence: 99%
“…This is also recognised by Murchland and Parkyn (2010), which describes how it is the assistive technology that provides enhanced status rather than the pupil. But in this study, it is not necessarily just the eye gaze technology itself that has enhanced status.…”
Section: Results Discussionmentioning
confidence: 99%
“…Disabled pupils' participation in classroom activities requires purposeful planning of their location in the classroom that can serve to avoid their location in isolated work spaces. Furthermore, the location in the classroom of a disabled pupil and his or her AT is of importance to their opportunities to interact with classmates and participate in classroom activities (Murchland and Parkyn 2010). However, Joackim and his classmates are not always in their regular classroom; quite often they move to other teaching areas, and the next lesson took place in a small auditorium.…”
Section: Location In the Classroommentioning
confidence: 99%
“…However, using AT is not only an individual modification, but it also depends on a variety of compatible connections and relationships, including human, technological, and organizational entities (Moser 2003;Söderström 2012). Moreover, several studies have found that AT assigned for use in school is sometimes used as intended, but quite often used less than intended, in unintended ways, or totally abandoned altogether (Murchland and Parkyn 2010;Söderström 2012). This may be due to technical barriers, but most often to human barriers connected to lack of competence or insecurity and attitudes (Lindsay 2010;Smith 2013;Rekkedal 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining eleven descriptive studies delineated the use and non-use of ICT (e.g. access, satisfaction, as well as which activities) in school activities (61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Methodological Aspectsmentioning
confidence: 99%